Collection and characterization of cassava germplasm in Comoros - Ferguson, Morag E.; Ntawuruhunga, P.; Fouad, M.O.; Hassane, O.K.M.; Charmila, M.A.; Hamza, A.A.; Mohamed, N.A.; Dieng, I.; Njukwe, E.; Shah, T. (Springer, 2024)
In Comoros, cassava plays a major food security role, however yields are low as few modern cultivars are grown. Prior to the introduction of new cultivars, and as a germplasm resource for breeders, germplasm collection missions were undertaken in the three largest islands; Ngazidja, Ndzouani and Mwali; and associated farmer knowledge documented. Cassava landraces were collected from 34 farms, and 17 key informant interviews conducted. Stakes of 79 collected landraces were planted for agro-morphological characterization. All landraces were genotyped using DaRTSeq technology and data analysed to identify duplicates. Genetic fingerprints of 46 unique landraces were co-analysed with 402 previously genotyped landraces and improved cultivars from Tanzania. From this set only one match was made with a very old cultivar, Aipin Valenca, from the Northern Zone in Tanzania. According to SNP data, germplasm from the three islands of Comoros were similarly related to one another, and more distantly related to germplasm from Tanzania. They were most closely related to germplasm from the Northern Zone in Tanzania, suggesting a possible historical introduction of germplasm from this area. Lower levels of diversity were observed on these islands, as well as the islands of Pemba and Zanzibar. This implies limited introduction and movement of cassava germplasm into the islands. Introductions of improved germplasm to Comoros is recommended with the simultaneous conservation of collected unique landraces. Two landraces with high market demand and reported tolerance to diseases were identified for further evaluation with a view to multiplication and distribution and incorporation into the breeding program.